2013
DOI: 10.1177/0363546513482302
|View full text |Cite
|
Sign up to set email alerts
|

Midterm Results of Comprehensive Surgical Reconstruction Including Sulcus-Deepening Trochleoplasty in Recurrent Patellar Dislocations With High-Grade Trochlear Dysplasia

Abstract: Sulcus-deepening trochleoplasty is a valid option for the primary surgical treatment of carefully selected patients with recurrent patellar dislocations with high-grade trochlear dysplasia type B and D. Concomitant etiological factors must be cautiously corrected in an associated procedure. Midterm follow-up showed satisfactory restoration of patellar stability and improvement of knee scores with no complication of subsequent arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
113
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 125 publications
(120 citation statements)
references
References 32 publications
5
113
0
2
Order By: Relevance
“…Whereas there are several studies that evaluated the combined reconstruction of the MPFL with a tibial tuberosity transfer or trochleoplasty [1,10,20,23], to our knowledge this is the first study that describes the technique and clinical outcome of a combined femoral derotation osteotomy and anatomical reconstruction of the MPFL in patients with patellofemoral instability and increased femoral anteversion.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas there are several studies that evaluated the combined reconstruction of the MPFL with a tibial tuberosity transfer or trochleoplasty [1,10,20,23], to our knowledge this is the first study that describes the technique and clinical outcome of a combined femoral derotation osteotomy and anatomical reconstruction of the MPFL in patients with patellofemoral instability and increased femoral anteversion.…”
Section: Discussionmentioning
confidence: 99%
“…Trochlear dysplasia has been directly associated with both recurrent patellar dislocation [18][19][20] and AKP [21,22] in patients with patellar instability, since it has been observed in 96 % of patients with PF disorders and in only 3 % of controls [15,22]. The surgical correction of trochlear dysplasia is done with the sulcusdeepening trochleoplasty procedure, in which the elevated groove is eliminated and the abnormal sulcus is deepened [23][24][25]; this can also rarely be enriched by the addition of patellar osteotomy in order to achieve a better congruency between the two articulating bones [26]. Some authors have also suggested that trochlear dysplasia may extend more distally to the intercondylar notch and therefore could be more frequent in patients with ACL tears due to a reduced intercondylar notch size that predisposes to ACL injury (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Ntagiopoulos et al followed 27 patients for an average of 7 years after sulcus deepening trochleoplasty for recurrent patellar instability. Sulcus angles decreased from an average of 152°-141° and there were no cases of patellar dislocation following the procedure 66 . At latest follow-up, no patients had radiographic evidence of patellofemoral osteoarthritis and knee pain and function improved significantly from pre-operative meas- Post-operative tibia fracture is also possible following tibial tubercle osteotomy.…”
Section: All Authors Contributed To Conception and Design Manuscriptmentioning
confidence: 86%